2010
DOI: 10.3109/02844311.2010.494416
|View full text |Cite
|
Sign up to set email alerts
|

Suzuki's pins and rubber traction for fractures of the base of the middle phalanx

Abstract: Basal fractures of the middle phalanx are uncommon, but difficult to treat. We have reviewed our first 20 patients using the Suzuki pins and rubber traction who were treated during an 8.5 year period (June 1998-December 2006) and 18 who were reviewed after 49 (range 17-116) months. All injuries were closed fractures of the base of the middle phalanx. Ten patients had a fracture of the volar lip and dorsal subluxation of the phalanx, one had a fracture of the dorsal lip, and seven had comminuted pilon fractures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 11 publications
3
19
0
4
Order By: Relevance
“…We found that the volar lip fractures were most frequent, which are in agreement with previously published papers [12,13]. Most fractures occurred during sports and men were more predominately injured (male:female ratio of 1.8) [5,12,[14][15][16].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found that the volar lip fractures were most frequent, which are in agreement with previously published papers [12,13]. Most fractures occurred during sports and men were more predominately injured (male:female ratio of 1.8) [5,12,[14][15][16].…”
Section: Discussionsupporting
confidence: 92%
“…ADL status from the objective evaluation resulted in the low score of one, which supports such a notion. Grip and pinch strength (93% and 100%, respectively) are also important markers of function and were as high in this study as in others [13,14,16,18,19]. Unfortunately, the objective evaluation only included 18 patients, which can account for the low TAM.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…En esta serie se obtiene un rango articular satisfactorio (90°de media), que está en consonancia con lo descrito en la literatura tanto por fijadores externos similares como el de Shen y col., 25 (83,9°), Finsen y col., 27 (72°) o Ruland y col., 28 (88°) así como por otros fijadores prefabricados como el de Kodama y col (91,2°), MacFarlane y col (85°) y Pélissier y col., (70°) 16,24,29 y es superior a otras publicaciones en las que se llevó a cabo cirugía abierta, como la de Cheah y col., 9 (75°).…”
Section: Discussionunclassified